Introducing the Shadow Play to Youngsters in Sarawak - Nur Afifah Vanitha, Abdullah (Universiti Malaysia Sarawak (UNIMAS), 2012)
Although Sarawak has been part of Malaysia since 1963, there are certain cultural aspects from the West Malaysia which remain foreign to thepeople of Sarawak. Such is the shadow play, a traditional theatre performance which is also part of the Malaysian cultural heritage. Most people of Sarawak have not had the opportunity to experience the live performance of the shadow play, while some have not heard of its name, ‘wayang kulit’. The unfamiliarity of this traditional theatre to the people of Sarawak, inspired the ‘Playing with Shadow Workshop’ held at the Sarawak Islamic Information Center(IIC) at Kuching on the 24th of March 2012. This workshop was intended as a pilot study by a group of researchers ii from the Faculty of Applied and Creative Arts (FACA), Universiti Malaysia Sarawak (UNIMAS)to create awareness towards the existence and extinction of ‘wayang kulit’ among youngsters. The FACA research team specially tailored this workshop to measure its effectiveness towards introducing and promoting interest towards shadow play among primary school children in Kuching. This article intends to share the design, content and the process of the shadow play workshop.